Advancement of ozone zero phenomenon by surface deterioration of stainless—steel electrode. (22nd July 2021) - Itoh, Haruo; Nagai, Takashi; Taguchi, Masaki; Teranishi, Kenji; Suzuki, Susumu
Abstract: It is well known that a fine powder is deposited on the surface of coaxial cylinder electrodes made from stainless steel and borosilicate glass in ozone generators. We inspected the fine powder and the stainless steel by x-ray diffraction and Auger electron spectroscopy to clarify the relationship between the gradual decrease in ozone concentration, i.e., ozone zero phenomena (OZP) produced in the ozone generator, and the deterioration of stainless steel. The results of x-ray diffraction for both specimens suggest that several oxides with iron, chromium and nickel are formed from the stainless steel exposed to an ozone–oxygen mixture and the discharge. In particular, FeO detected by x-ray diffraction analysis means that the temperature of the surface of stainless steel and the powder reaches at least 843 K owing to the generation of heat by discharge and oxidation of the fine powder and electrode surface despite the inside of electrodes being refrigerated with circulating water. This temperature is much higher than the 453 K estimated in our previous work as a threshold temperature of the thermal decomposition of ozone by model experiments using a simulated ozone generator during the OZP. On the other hand, Auger electron spectroscopy is carried out in combination with the repeated tracing of the OZP, and we investigate whether oxygen atoms penetrate in the depth direction of the stainless steel. During this process, we observed serious OZP, meaning the ozone concentration at the outlet of the ozone generator is almost zero for 40–50 h continuously following the gradual decrease in ozone concentration. The penetration of oxygen atoms into the stainless-steel bulk is considered as the start of the collapse of the original passivation film covering on the surface of stainless steel. After the process, i.e., the cessation of the OZP, the formation of a new thin layer instead of the passivation film is observed with the coexistence of a strong oxidizer, i.e., ozone and atomic oxygen and the heat produced by discharge in the ozone generator. However, the recovered ozone concentration is realized up to half of the peak value in the measurement. This process corresponds to the recovery of the ozone concentration after the OZP. Hence, we concluded that the OZP is advanced by the thermal decomposition of ozone accompanied by the deterioration of the stainless-steel surface by ozone oxidation.